Ultra-wideline 14N solid-state NMR as a method for differentiating polymorphs: glycine as a case study1. Issue 28 (28th July 2015) - Veinberg, Stanislav L.; Friedl, Zachary W.; Harris, Kristopher J.; O'Dell, Luke A.; Schurko, Robert W.
<x xml:space="preserve">Abstract</x> 14N solid-state NMR is useful for differentiating polymorphs and chemically distinct nitrogen-containing compounds. A case study of glycine is presented.